MICRO RNA: A PROSPECTIVE DIAGNOSTICBIOMARKER IN ALZHEIMER’S DISEASE - Syeda Uroosa Hashmi; Ameer Haider Ali (Baqai Journal of Health Sciences)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disorder, characterized by cognitive decline that impairs individuals' ability to perform normal activities independently. Epidemiological data indicates that over 50 million people globally are affected by AD, and no existing drugs have successfully reversed its progression. MicroRNAs (miRNAs), small non-coding RNA molecules consisting of approximately 22 nucleotides, play a critical role in modulating intracellular protein expression at the post-translational level through translational degradation. Studies have shown varying concentrations of miRNAs in the peripheral and central nervous tissues of AD patients compared to control groups. This research explores the mechanisms and roles of miRNAs in gene regulation related to AD and highlights their potential as therapeutic agents for neurodegenerative diseases.